Perceptions of accountability for the transfer of training by leadership trainers - Susanne Wisshak; Dorothee Barth (International Journal of Training and Development, 2021)
Schlenker's model of responsibility was used in this study to investigate to what extent leadership trainers consider themselves accountable for the transfer of training. We conducted 15~semi-structured interviews and evaluated the answers using qualitative content analysis. With respect to the responsibility links of Schlenker's model, the trainers described two out of three links as being rather strong. The interview data suggest that transfer-enhancing strategies were mostly clear to the trainers. They also reported feeling personally obliged to support trainees in their transfer efforts. Regarding the third link, the trainers perceived limited control over several transfer determinants. They explained that they could facilitate transfer but not produce it. The trainers identified the trainees, their supervisors, and the organisations as other responsible parties. The concept of trainers as transfer managers was scarcely reported among the data. Our findings suggest that client organisations could strengthen accountability by setting adequate and feasible training objectives and by monitoring their achievement. We discuss the theoretical and practical implications with regard to the promotion of transfer.
Keywords: 650